Applicate Analytic Hierarchy Process for Evaluation of Biomass Plant Location - พันธุ์คง วรพจน์; มณีศรี ธรินี; มณีศรี ชวลิต (Engineering and Technology Horizons, 2020)
This research studies and evaluates the plant location alternatives of biomass from cassava roots in Phitsanulok province. The alternatives are three districts such as Chat Trakan, Wat Bot, and Wang Thong. We apply the Analytic Hierarchy Process (AHP) to evaluate the important weight factors which include raw materials source, transportation, infrastructure, power and fuel source, and labors. The raw materials source is the most important factor from the expert’s decision because the raw materials source affect to product cost and the cost of long term commitment. The result shows that Wang Thong district is the most suitable for construct plant of biomass from cassava roots in this province with 0.40 of the important point. While Chat Trakan district and Wat Bot district has 0.33 and 0.27 respectively.